The philosophy of Tim Burton - McMahon, Jennifer L. (University Press of Kentucky, 2014)
Director and producer Tim Burton impresses audiences with stunning visuals, sinister fantasy worlds, and characters whose personalities are strange and yet familiar. Drawing inspiration from sources as varied as Lewis Carroll, Salvador Dalí, Washington Irving, and Dr. Seuss, Burton's creations frequently elicit both alarm and wonder. Whether crafting an offbeat animated feature, a box-office hit, a collection of short fiction, or an art exhibition, Burton pushes the envelope, and he has emerged as a powerful force in contemporary popular culture. In The Philosophy of Tim Burton, a distinguished.